2004
DOI: 10.1176/jnp.16.4.456
|View full text |Cite
|
Sign up to set email alerts
|

Prefrontal Cortical Dysfunction in Abstinent Cocaine Abusers

Abstract: The anterior cingulate cortex (ACC) and lateral prefrontal (LPFC) cortex are brain regions important to executive cognitive functions (ECF). We determined ACC and LPFC function in 23-day abstinent cocaine abusers using positron emission tomography (PET H 2 15 O) during performance of a modified version of the Stroop Task. Cocaine abusers showed less activation than non-drug-using comparison subjects in the left ACC and the right LPFC and greater activation in the right ACC. Average amount of cocaine used per w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
104
1
4

Year Published

2006
2006
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 207 publications
(123 citation statements)
references
References 35 publications
(44 reference statements)
13
104
1
4
Order By: Relevance
“…The general pattern of poorer inhibitory control in cocaine users is consistent with the extant literature (Bolla et al, 1999;Fillmore and Rush, 2002;Hester and Garavan, 2004), although intact performance has also been reported (Bolla et al, 2004;Goldstein et al, 2001;Hoff et al, 1996). It is possible that some of the cause of inconsistency lies with sampling power, primarily the number of observations, as both current tasks indicate a significant cocaine-related deficit when inhibitory performance is averaged across within-task conditions.…”
Section: Inhibitory Controlsupporting
confidence: 84%
See 1 more Smart Citation
“…The general pattern of poorer inhibitory control in cocaine users is consistent with the extant literature (Bolla et al, 1999;Fillmore and Rush, 2002;Hester and Garavan, 2004), although intact performance has also been reported (Bolla et al, 2004;Goldstein et al, 2001;Hoff et al, 1996). It is possible that some of the cause of inconsistency lies with sampling power, primarily the number of observations, as both current tasks indicate a significant cocaine-related deficit when inhibitory performance is averaged across within-task conditions.…”
Section: Inhibitory Controlsupporting
confidence: 84%
“…Previous studies have indicated that cocaine users have a hypoactive error-related neural response (Kaufman et al, 2003;Kubler et al, 2005), particularly in the ACC region. It remains unclear how this hypoactivity might contribute to the more general cognitive control problem identified in this population (Bolla et al, 2004;Di Sclafani et al, 2002;Fillmore and Rush, 2002;Goldstein et al, 2001), which suggests a broader dysfunction in fronto-parietal top-down control networks. Two error-related processes were chosen to examine the potential influence of a hypoactive error-related neural response: error awareness and post-error cognitive control.…”
Section: Introductionmentioning
confidence: 95%
“…The improvement in prediction ability of the model after the addition of the HDRS scores suggests that affective state contributes to treatment compliance. This is not surprising as decreased activity in the cingulate cortex and other prefrontal regions has been reported in both depressed individuals and cocaine-dependent individuals with impaired performance on the Stroop (Mayberg, 1997;Bolla et al, 2004). Most reports of neuropsychological testing in cocaine-dependent subjects have been completed when subjects are in varying degrees of abstinence (Manschreck et al, 1990; O'Malley et al, 1992; Mittenberg and Motta, 1993;Beatty et al, 1995;Bolla et al, 1998Bolla et al, , 1999Bolla et al, , 2000.…”
Section: Discussionmentioning
confidence: 99%
“…An fMRI study of cocaine abusers, using a modified version of the Goldman Stroop task, demonstrated less activation of the left ACC and right lateral PFC and increased activation of the right ACC compared to controls (Bolla et al, 2004). Subjects with the highest cocaine use before the study showed the lowest activation of prefrontal structures suggesting that cocaine use compromises the activation of the prefrontal regions involved in executive function (Bolla et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…These include a depletion, and reduced functioning of D2 receptors in the orbitofrontal cortex, cingulate gyri and striatum (Volkow et al, 1993(Volkow et al, , 1997(Volkow et al, , 1999Martinez et al, 2007Martinez et al, , 2009), dysfunctions in frontal brain regions including orbitofrontal, lateral prefrontal and anterior cingulate cortex (Bolla et al, 2001(Bolla et al, , 2003(Bolla et al, , 2004, as well as anterior cingulate and cerebellum (Hester and Garava, 2004). A reduced uptake of l-dopa (the precursor to dopamine) has also been reported in abstinent cocaine users .…”
Section: Introductionmentioning
confidence: 99%